The Congregational Independents and the Cromwellian Constitutions - Cook, Sarah Gibbard (Church history, 1977)
The Protectorate of Oliver Cromwell was a practical experiment in government, but it was an experiment guided by more than practicality alone. For its first three years, it rested heavily on a single ecclesiastical party, the Congregational Independents. This was the party of the preachers John Owen, Philip Nye, Thomas Goodwin, and their fellows and followers. They did not rule alone, but for three years they managed to dominate the governing coalition. They supplied the implicit ideological basis and the explicit personal support for the establishment of the Protectorate, the reign of the major generals, and the refusal of the Protector to accept a crown. Briefly but with lasting effects, England experienced the political consequences of a Congregational Independent regime.